Advancements in the application of optical coherence tomography in hepatopancreatobiliary systems: a comprehensive review - Liming Yao; Ying Pan; Jiang Yu; Kaiming Leng (European Journal of Medical Research)
Abstract Optical coherence tomography (OCT) has emerged as a transformative diagnostic tool in the realm of uncertain biliary strictures within the digestive system. Its superiority over conventional methods lies in its ability to provide submucosal assessments and real-time, wide-ranging tissue evaluations. The latest advancement in OCT technology, exemplified by the NVision Volumetric Laser Endomicroscopy (VLE) system, has significantly enhanced imaging quality and microstructure delineation, particularly in characterizing the intricate anatomy of pancreaticobiliary ducts. In recent studies, OCT has demonstrated remarkable capabilities in overcoming challenges posed by stents, inflammation, and fibrosis, setting it apart as a versatile diagnostic adjunct. Although the safety and feasibility of OCT have been extensively validated, its clinical integration demands further validation through large-scale trials and comparative studies. Ongoing technical innovations and refinements in OCT technology underscore its potential to revolutionize diagnostic precision in hepatobiliary sciences. In summary, OCT stands at the forefront of cutting-edge diagnostic methodologies for uncertain biliary strictures, offering unparalleled insights into tissue microstructures. Its seamless integration with complementary modalities, ongoing technical refinements, and the advent of ultrathin cholangioscopes collectively position OCT as a promising avenue for advancing diagnostic capabilities in hepatobiliary medicine. A literature-based review was conducted via PubMed and Web of Science to extract and synthesize diagnostic performance and structural criteria of OCT in hepatobiliary applications.